Times have changed: Parent perspectives on children's free play and sport. (September 2017) - Watchman, Tina; Spencer-Cavaliere, Nancy
Abstract: Objectives: The purpose of this study was to examine parents' perspectives of children's free play and sport using a socioecological lens. Design: Qualitative, interpretive description. Method: Data were collected using semi-structured interviews with 12 parents of children in middle childhood (ages 8–10). Interviews were transcribed verbatim and analyzed inductively according to interpretive description and deductively using a socioecological model. Results: The overarching theme, 'times have changed', captured the ways in which children's sport and free play have evolved since parents' own childhoods. Within this overarching theme, two primary themes were identified: 1) not so 'free' play and 2) the privileging of sport. Conclusions: Both free play and sport were viewed as important to middle childhood, however, experiences gained in children's sport were seen to be of greater value to the overall development of children, and were therefore prioritized. Ultimately our findings demonstrate the complexity of parenting and the pressures exerted from various levels of influence on the decisions they make with regard to their children's wellbeing in the contexts of free play and sport. How to inform and best support parents in this process remains a significant challenge in moving forward. Highlights: Interpretive description is a useful approach to learn about parent perspectives. Parents may not recognize the benefits of free play in middle childhood. Children's participation in sport is prioritized over play for developmental reasons. Parents' desire for children's sport sampling conflicts with pressures to specialize. Collaboration among stakeholders is needed to rethink how sport and play can co-exist.